Suicidal behaviors among adolescents in juvenile detention: role of adverse life experiences. - Madhav P Bhatta; Eric Jefferis; Angela Kavadas; Sonia A Alemagno; Peggy Shaffer-King (PLoS ONE)
Purpose The purpose of this study was to assess the influence of multiple adverse life experiences (sexual abuse, homelessness, running away, and substance abuse in the family) on suicide ideation and suicide attempt among adolescents at an urban juvenile detention facility in the United States. Materials and methods The study sample included a total of 3,156 adolescents processed at a juvenile detention facility in an urban area in Ohio between 2003 and 2007. The participants, interacting anonymously with a voice enabled computer, self-administered a questionnaire with 100 items related to health risk behaviors. Results Overall 19.0% reported ever having thought about suicide (suicide ideation) and 11.9% reported ever having attempted suicide (suicide attempt). In the multivariable logistic regression analysis those reporting sexual abuse (Odds Ratio = 2.75; 95% confidence interval  = 2.08-3.63) and homelessness (1.51; 1.17-1.94) were associated with increased odds of suicide ideation, while sexual abuse (3.01; 2.22-4.08), homelessness (1.49; 1.12-1.98), and running away from home (1.38; 1.06-1.81) were associated with increased odds of a suicide attempt. Those experiencing all four adverse events were 7.81 times more likely (2.41-25.37) to report having ever attempted suicide than those who experienced none of the adverse events. Conclusions Considering the high prevalence of adverse life experiences and their association with suicidal behaviors in detained adolescents, these factors should not only be included in the suicide screening tools at the intake and during detention, but should also be used for the intervention programming for suicide prevention.